Pediatric Epilepsy Mechanisms: Expanding the Paradigm of Excitation/Inhibition Imbalance - Li-Rong Shao; Christa W. Habela; Carl E. Stafstrom (MDPI AG, 2019)
Mechanisms underlying seizures and epilepsy have traditionally been considered to involve abnormalities of ion channels or synaptic function. Those considerations gave rise to the excitation/inhibition (E/I) imbalance theory, whereby increased excitation, decreased inhibition, or both favor a hyperexcitable state and an increased propensity for seizure generation and epileptogenesis. Several recent findings warrant reconsideration and expansion of the E/I hypothesis: novel genetic mutations have been identified that do not overtly affect E/I balance; neurotransmitters may exert paradoxical effects, especially during development; anti-seizure medications do not necessarily work by decreasing excitation or increasing inhibition; and metabolic factors participate in the regulation of neuronal and network excitability. These novel conceptual and experimental advances mandate expansion of the E/I paradigm, with the expectation that new and exciting therapies will emerge from this broadened understanding of how seizures and epilepsy arise and progress.